1996
DOI: 10.1007/s002130050096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of destruction of the 5-hydroxytryptaminergic pathways on behavioural timing and "switching" in a free-operant psychophysical procedure

Abstract: This experiment examined the effect of destruction of the ascending 5-hydroxytryptaminergic (5HTergic) pathways on performance in a free-operant timing schedule. Rats received either injections of 5,7-dihydroxytryptamine into the dorsal and median raphe nuclei or sham lesions. They were trained to press levers for a sucrose reinforcer. Training sessions consisted of 40, 50-s trials in which reinforcers were available on a variable-interval 25-s schedule; in the first 25 s of each trial, reinforcers were only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
16
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
8
16
0
Order By: Relevance
“…The pattern of responding seen in this experiment is consistent with numerous previous studies with this schedule (Stubbs 1976(Stubbs , 1979Bizo and White 1994a, 1994bAl-Zahrani et al 1996Chiang et al 1998Chiang et al , 1999. In both the "unconstrained-switching" and "con- Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The pattern of responding seen in this experiment is consistent with numerous previous studies with this schedule (Stubbs 1976(Stubbs , 1979Bizo and White 1994a, 1994bAl-Zahrani et al 1996Chiang et al 1998Chiang et al , 1999. In both the "unconstrained-switching" and "con- Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Significance of difference from vehicle treatment: *P<0.05 strained-switching" versions of the schedule, response rate on lever A declined and response rate on lever B increased during the course of the trial, this being reflected in an increasing percentage of total responding being devoted to lever B (%B) as the trial progressed. The relationship between %B and time within the trial was well described by a logistic function, the goodness of fit of the function seen in this experiment being similar to that seen in many previous studies (Bizo and White 1994a, 1994bAl-Zahrani et al 1996Chiang et al 1998Chiang et al , 1999. In this experiment, as in several previous studies (Fetterman and Killeen 1995;Al-Zahrani et al 1996Chiang et al 1998Chiang et al , 1999, there was a progressive decline in overall response rate during the course of the trial.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This trend, which has been reported in several previous studies (e.g. Fetterman and Killeen 1995;Al-Zahrani et al 1996Chiang et al 1998), coincides with a gradual decline in overall response rate during the trial, a common finding in this schedule (Chiang et al 1998) and other related schedules (Fetterman and Killeen 1995;Stubbs 1976). It has been suggested that this may be due to a decay of arousal from a high level induced by the initial presentation of the operanda at the start of the trial (Killeen et al 1997; see also Killeen 1979).…”
Section: Discussionsupporting
confidence: 64%